Computation of the effective lamination stack's behavior considering the contact simulation with a multi-scale homogenization - Luchscheider, Vera; Maidorn, Mischa; Willner, Kai (Joint 11th World Congress on Computational Mechanics, WCCM 2014, the 5th European Conference on Computational Mechanics, ECCM 2014 and the 6th European Conference on Computational Fluid Dynamics, ECFD 2014, 2014)
The influence of the lamination stack on the mechanical behavior of an electrical machine is significant, especially for lightweight designs. Information about the stack's behavior is relevant for a proper calculation of the whole motor. This behavior is dependent on the contact between the single sheets. This paper aims to show that the normal contact behavior can be simulated with the elastic model of Bush, Gibson and Thomas, a plastic term depending on deformation of the highest peaks and a viscous term. The tangential slip is described through a micro-macro model. These models can be used in a representative volume element and consequently for a multi-scale homoge-nization. A material model of the whole lamination stack can be identified by loading the representative volume element with different deformations.
Keywords: Contact mechanics; Homogenization; Lamination stack